Behaviour matters: improving energy efficiency in informal settlements - Aurelia Figueroa (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
By 2022, two billion people will be living in informal settlements according to the United Nations. Although per capita energy consumption in informal settlements is comparatively low, the benefits of energy efficiency uptake – enhanced energy system sustainability, economic development, social development, environmental sustainability, and increased prosperity (International Energy Agency [IEA], 2014) – stand to equally benefit these communities. Yet despite these benefits, informal settlement households – as so many others – have been slow in taking up energy-efficient technologies. This can be partly attributed to behavioural barriers: Consumers often do not invest in energy efficiency in an economically rational manner. Recent research findings point to effective means of implementing behavioural insights for energy efficiency in informal settlements. Building upon this precedence, governments, international organisations and implementing agencies should en¬courage the application of potentially low-cost behavioural insights to energy efficiency initiatives in informal settlements to improve intervention efficacy. It is easy for energy efficiency to be lost in the challenging demands of daily life in informal settlements – sourcing water, managing irregular employment opportunities, or basic health and safety concerns, compounded by risk aversion and the discounting of future-based benefits. This is why it is essential to integrate behavioural insights to facilitate energy-efficiency uptake. This may be done, for example, by making information on energy efficiency simple and meaningful, by focussing on context-specific benefits, by bringing the economic benefit of uptake closer to the consumer while spacing the cost over time, or by appealing to social norms. While most evidence on the importance of behavioural insights for energy efficiency stems from the OECD member country context, the topic is equally relevant in the developing country informal settlement context. Here, the cost-benefit analysis of energy efficiency is further complicated by the fact that many households informally consume electricity without paying for it or by paying a flat rate. This presumably removes the traditional pecuniary motivation – electrical bill savings – upon which to influence energy-efficiency implementation. What entry points then exist for energy-efficient products which invariably have a higher upfront purchase cost when there are – prima facie – no financial benefits to be realised? The higher durability of energy-efficient products in the context of the instable electricity supply occurring in many developing countries could be an obscured benefit. It accrues not just at the societal level but also at the individual level, further building the economic case for energy-efficiency uptake.
Keywords: 330; Klimawandel; Energie